The roles of surface ultrastructures in the predatory life cycle of Bdellovibrio bacteriovorus - Evans, Katy (2007)
Bdellovibrio bacteriovorus is a ubiquitous Gram-negative 8-proteobacterium that is predatory on other Gram negative bacteria. It's prey includes many pathogenic bacteria, including E. coli, Salmonella, Proteus and Pseudomonas species; as such, there is much interest in the study of Bdellovibrio with a view to its potential use as an alternative antimicrobial therapy.